GAMBARAN AKTIVITAS ENZYME ALANINE TRANSAMINASE (ALT) PADA PENGKONSUMSI MINUMAN BERALKOHOL - Ainun Qolbi Wasdili, Fini; Aslamiyah, Suaibatul; Romlah, Sitti (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Alcohol consumption is the third largest risk factor in the world as a cause of disease and disability. There are various types of diseases caused by alcohol consumption, one of which is impaired liver function. Liver function disorders can be indicated by an increase in enzyme activity, one of which is the ALT enzyme. The purpose of this study was to describe the activity of the ALT enzyme in alcoholic beverage consumers. Examination of blood samples has been carried out on alcoholic drink consumers in the